2005
DOI: 10.1021/ic051090h
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectra of CH3−CrH, CH3−WH, CH2WH2, and CH⋮WH3Formed by Activation of CH4with Cr and W Atoms

Abstract: Laser-ablated W atoms react with CH4 in excess argon to form the CH3-WH, CH2=WH2, and CH[triple bond]WH3 molecules with increasing yield in this order of product stability. These molecules are identified from matrix infrared spectra by isotopic substitution. Tungsten methylidene and methylidyne hydride molecules are reversibly interconverted by alpha-H transfers upon visible and ultraviolet irradiations. Matrix infrared spectra and DFT/B3LYP calculations show that CH[triple bond]WH3 is a stable molecule with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
164
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(197 citation statements)
references
References 41 publications
32
164
1
Order By: Relevance
“…The observed photoreversible variations in the intensities of the product absorptions suggest that the product responsible for the i absorptions converts to those responsible for the m and y absorptions on visible irradiation and vice versa in UV irradiation. Similar photoreversibility was observed previously in the matrix reaction of Mo with CH 4 ; CH 3 –MoH converted to CH 2 MoH 2 and HCMoH 3 on visible irradiation via H-migration from C to Mo, and vice versa on UV irradiation via H-migration from Mo to C …”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The observed photoreversible variations in the intensities of the product absorptions suggest that the product responsible for the i absorptions converts to those responsible for the m and y absorptions on visible irradiation and vice versa in UV irradiation. Similar photoreversibility was observed previously in the matrix reaction of Mo with CH 4 ; CH 3 –MoH converted to CH 2 MoH 2 and HCMoH 3 on visible irradiation via H-migration from C to Mo, and vice versa on UV irradiation via H-migration from Mo to C …”
Section: Resultssupporting
confidence: 86%
“…Spectral assignments have been carried out on the basis of spectral variation by deuteration, correlation with the computed values, and previous studies on reactions of metal atoms with methane and methyl halides. The observed i absorption at 1688.6 cm –1 is assigned to the Mo–H stretching mode of the insertion complex (CH 3 CH 2 –MoH) with its D counterparts at 1211.6 cm –1 (Table and S1). The H/D ratio 1.394 is appropriate for the vibrational mode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Do the bond dissociation energies in Table 4 imply that the NTh and NU bonds are anomalously strong? The analysis is complicated by the agostic interactions that are present in some of the compounds, the influence of which will contaminate the bond dissociation energies evaluated here (note that agostic interactions have little effect on CM distances41). The NHf and NW bonds are stronger than their CHf and CW counterparts by 151 or 148 kJ mol −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These studies were extended to the accessible actinide metal atoms Th and U for the preparation of the first actinide methylidene species HXAnϭCH 2 (X ϭ H, F, Cl, Br) (38)(39)(40)(41). Although Mo and W reactions also formed the analogous H 2 XM'CH methylidynes (42)(43)(44)(45)(46), the H 2 XU'CH counterparts were energetically too high to be produced in these experiments (40). However, very recent investigations with the heavy metals Zr, Hf, and Re in trihalomethane reactions have demonstrated that the highly exothermic driving force for halogen transfer from carbon to heavy metal fosters the formation of the low-energy, very stable trihalo metal carbynes (47,48).…”
mentioning
confidence: 99%